Effects of microgravity on neural crest stem cells - Han, Yilin; Barasa, Povilas; Zeger, Lukas; Salomonsson, Sara B.; Zanotti, Federica; Egli, Marcel; Zavan, Barbara; Trentini, Martina; Florin, Gunnar; Vaerneus, Alf; Aldskogius, Håkan; Fredriksson, Robert; et al. (Frontiers in Neuroscience, 2024)
Exposure to microgravity (µg) results in a range of systemic changes in the organism, but may also have beneficial cellular effects. In a previous study we detected increased proliferation capacity and upregulation of genes related to proliferation and survival in boundary cap neural crest stem cells (BC) after MASER14 sounding rocket flight compared to ground-based controls. However, whether these changes were due to µg or hypergravity was not clarified. In the current MASER15 experiment BCs were exposed simultaneously to µg and 1 g conditions provided by an onboard centrifuge. BCs exposed to µg displayed a markedly increased proliferation capacity compared to 1 g on board controls, and genetic analysis of BCs harvested 5 h after flight revealed an upregulation, specifically in µg-exposed BCs, of Zfp462 transcription factor, a key regulator of cell pluripotency and neuronal fate. This was associated with alterations in exosome microRNA content between µg and 1 g exposed MASER15 specimens. Since the specimens from MASER14 were obtained for analysis with one week's delay, we examined whether gene expression and exosome content were different compared to the current MASER15 experiments, in which specimens were harvested 5h after flight. The overall pattern of gene expression was different and Zfp462 expression was down-regulated in MASER14 BC µg compared to directly harvested specimens (MASER15). MicroRNA exosome content was markedly altered in medium harvested with delay compared to directly collected samples. In conclusion, our analysis indicates that even short exposure to µg alters gene expression, leading to increased BC capacity for proliferation and survival, lasting for a long time after µg exposure. With delayed harvest of specimens, a situation which may occur due to special post-flight circumstances, the exosome microRNA content is modified compared to fast specimen harvest, and the direct effects from µg exposure may be partially attenuated, whereas other effects can last for a long time after return to ground conditions.